Forty years of Semina: Ciências Agrárias - Agrárias, Editorial Semina (2018)
In 2018, Semina, the cultural and scientific magazine of the State University of Londrina (UEL), is celebrating 40 years of operation. The first edition of April/June 1978 was published under the management of the Dean Professor Dr. Oscar Alves and the Vice-Dean Professor Dr. Pedro Vasconcelos Barros, with an Editorial Board comprised of President Professor Theobaldo Cioci Navolar, Director Professor Enoque Balbino Lima, and Members of the Editorial Board Professor Maria Luzel de Oliveira Cauduro, Professor Dr. Jesus Berbel, Professor Leange Severo Alves, and Professor Aldo Matsumoto. With its motto “everything that is planted, grows,” Semina originated as an organ of cultural and scientific dissemination of UEL, an institution located in a region with one of the richest soils in the world, Northern Paraná. In addition, Semina means seed, a word derived from the Latin words terrain and seminis. Thus, the UEL periodic, which means “Seeds” in plural, symbolizes the goal of sowing culture and science in the minds of its readers by disseminating works and activities in all fields of knowledge and culture. The history of the Semina periodic complements the history of the University itself, which was founded on January 28, 1970 by a decree of the then governor of Paraná, Paulo Pimentel. Since its first edition in 1978, the Semina magazine has been following the scientific and cultural development of our University. In Semina’s 40 years of existence, UEL has grown considerably, with an increase in the number of its faculty, administrative staff, and students; this is a result of the growing demand for development in the region and the creation of new latu sensu and stricto sensu undergraduate and postgraduate courses, which has led to a consequent increase in the intellectual production of the institution. The internal growth of UEL and the region increased the demand for internal and external scientific production, which triggered a natural pressure for restructuring and revision of the periodic’s capacity to meet the changes and demands related to this development. Thus, in 1987, Semina began to publish specific issues for each of the four major areas of knowledge: Agrarian Sciences, Biological and Health Sciences, Social and Human Sciences, and Exact and Technological Sciences. Semina: Ciências Agrárias was effectively created in its current form in 2001, with a new ISSN record, and published two issues per year until 2003, four until 2011 and, six or more per year, including supplementary issues, since 2012. With this new division, the current Semina: Ciências Agrárias was indexed in the ISI of Thomson Reuters (SCIE), CAB Abstracts, Chemical Abstracts (CAS), Food Science and Technology (FSTA), AGRIS DATABASE, SCOPUS, and DOAJ, thus offering new opportunities for the publication of scientific papers with the guarantee of wide national and international dissemination. In 2009, Semina: Ciências Agrárias started to be published by the Open Journal Systems (OJS) a software developed for the construction and management of electronic journal publications and its papers were made freely available in the Portal of Scientific Journals of UEL. It began receiving submissions through this electronic system, which increased its access and streamlined the procedure. Since then, Semina: Ciências Agrárias has been ranked by the Journal Citation Reports (JCR) of Thomson Reuters with an initial impact factor of 0.182. Currently, the impact factor is 0.309 for JCR and 0.350 for SJR (Scientific Journal Rankings) of the editor SCImago. Due to its performance in these important indexes of the Agrarian Sciences and the ease of electronic submission, there was a great increase in the number of papers submitted to be evaluated for publication. This increase allowed an improved selection of published papers and, since 2005, publication in English has been prioritized. Thus, the number of papers published per issue increased to 15 in 2005, to 40 in 2011, and in to 50 in 2013, a number maintained until today. From 2010, Semina: Ciências Agrárias started to use DOI (Digital Object Identifier), an identifier of intellectual property with a unique and exclusive standard code consisting of numbers and letters that enables the creation of a permanent link to a published digital document, easing the access to papers published online. In June 2010, Semina: Ciências Agrárias received its first impact factor evaluation in the ISI Web of Knowledge database. It was observed that the evolution of the magazine occurred in parallel to the growth of UEL’s three Post-Graduate Programs in the wide area of Agricultural Sciences: Food Science, Animal Science, and Agronomy. In January 2018, UEL completed 48 years; the undergraduate program in Veterinary Medicine has run for 45 of these years, and Semina: Ciências Agrárias for 40 years, both making a significant contribution to the history of the institution's development. Throughout its 45 years of existence, the undergraduate program in Veterinary Medicine has grown considerably, establishing from the beginning strategies for the scientific and technological development of the institution and the region. Therefore, the Postgraduate program in Animal Health was created, later evolving to the current Masters and Doctorate Programs in Animal Science, with the participation of professors of the Department of Animal Sciences. A highlight of the periodic's long history has been the important participation of the Chief Editor, Professor Dr. Odilon Vidotto, researcher and recognized professor in Parasitology and Parasitic Diseases. In addition to the growth and improvement in the Animal Science, Agronomy and Food Science Post-Graduate Programs at UEL, the impact of Semina: Ciências Agrárias on the national scientific community has been significant, publishing papers from all regions of the country, most of them from several Postgraduate Programs in the areas of Agrarian, Veterinary, Biological, and Health studies. Currently, the periodic publishes bimonthly original and review papers, case reports, and communications from the wide field of Agrarian Sciences (Agronomy, Food Science and Technology, Veterinary Medicine, and Animal Husbandry). In 2018, on the online Electronic Publishing System for Magazines (SEER), Semina completed nine years of operation, showing an upward trajectory of publications. From 1978 to 1987, 257 papers were published, and from 2009 to 2018 (the online period) 2,858 papers were published; in total, 3,840 papers were published so far. This greater number of publications coincided with the creation by Semina of its own bureau and the hiring of a librarian exclusive for the journal. Librarian Edilaine Aparecida Soares is responsible for the bureau's work, standardization, and publication of papers. The online system allows access for more than seven thousand users (authors, evaluators, and editors) and currently has 10,260 users and 4,576 ad hoc evaluators registered. To celebrate the 40 years of Semina: Ciências Agrárias, the current Chief Editor Professora Dra. Ivone Yurika Mizubuti, the on-leave Editor-in-Chief, Professor Dr. Odilon Vidotto, and the Managing Editors Professores Drs. Carmen Silvia Vieira Janeiro Neves and Professora Dra. Elza Iouko Ida, as well as the 20 section editors, would like to thank the authors, evaluators, and the editing team for their important contribution during the entire course of the journal. Their work has resulted in the performance already reported and, in the future, will certainly help Semina: Ciências Agrárias evolve to the highest levels.